EKSPLORASI PERSEPSI NASABAH TERHADAP FAKTOR-FAKTOR PEMBENTUK MINAT PEMBIAYAAN BANK SYARIAH: ANALISIS STATISTIK DESKRIPTIF - Saputra, Rega; Jaharuddin, Jaharuddin (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to systematically describe the perceptions of Islamic bank customers in Indonesia regarding the factors that influence their interest in using Islamic bank financing, which include trust, promotion, service quality, and Islamic religiosity, using a descriptive statistical approach. An exploratory descriptive approach was used in this study. The research sample consisted of 538 Islamic bank customers in Indonesia who were selected using purposive sampling. Data were collected through a structured questionnaire with a 5-point Likert scale that had been tested for validity and reliability. Data analysis was performed using descriptive statistics to describe the characteristics of the respondents and their perceptions of the research variables through minimum, maximum, mean, and standard deviation values. The research findings show that trust, promotion, service quality, and Islamic religiosity are in the high category with relatively homogeneous perceptions among respondents, thus playing a significant role in encouraging customer interest in Islamic bank financing. The low standard deviation value also indicates that the influence of these four variables is positive and relatively stable among respondents. This study contributes theoretically to the study of Islamic banking in Indonesia and has practical implications as a guide for Islamic banks, particularly BSI, in increasing the interest of young customers aged 20–25 years, the majority of whom are students, in Islamic financing.Keywords : Sharia bank, interest, financing, strategy